Programma: 18 januari: Franco 7 Le Tpok Jazz; 19 januari: Thunder in the House; 20 januari: Coupe Cubana; 21 januari: Sister Ray; 22 januari: Club Liever Live; 26 januari: Thunder in the House; 27 januari: Nuit Arabe; 28 januari: The Jack of Hearts, Fetus Productions (1989)
Programma: 18 januari: Franco 7 Le Tpok Jazz; 19 januari: Thunder in the House; 20 januari: Coupe Cubana; 21 januari: Sister Ray; 22 januari: Club Liever Live; 26 januari: Thunder in the House; 27 januari: Nuit Arabe; 28 januari: The Jack of Hearts, Fetus Productions.